O ensino da metodologia projetual no desenvolvimento de produtos de moda: um estudo de caso na Universidade Estadual de Londrina - Miotto, Thassiana de Almeida [UNESP] (2014)
This research aimed to facilitate the learning of design methodology in the course of Fashion Desing at the State University of Londrina. From the investigation of how knowledge is constructed and the relationship established between methodologies - Project and Science - used in this context, were proposed strategies interventions during the project action of students, uniting the methodologies concepts analyzed, in order to facilitate the learning. The survey data were obtained through questionnaires and direct observation of processes, their results were tabulated by qualitative research techniques and, at the end of the analysis, were proposed a conceptual schema contemplating learning situations in the design process fashion products